2013
DOI: 10.1371/journal.pone.0053975
|View full text |Cite
|
Sign up to set email alerts
|

Poor Reproducibility of Allergic Rhinitis SNP Associations

Abstract: Replication of reported associations is crucial to the investigation of complex disease. More than 100 SNPs have previously been reported as associated with allergic rhinitis (AR), but few of these have been replicated successfully. To investigate the general reproducibility of reported AR-associations in candidate gene studies, one Swedish (352 AR-cases, 709 controls) and one Singapore Chinese population (948 AR-cases, 580 controls) were analyzed using 49 AR-associated SNPs. The overall pattern of P-values in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…35 For examples, genetic variations with genome-wide significance showed poor consistency across GWAS of major depression 36 and allergic rhinitis. 37 Hence, we looked for evidence of replication of SNPs from our first GWAS. Secondly, the ALL population was not ideal to reveal interactive effects of SNP and the cumulative dose of GCs, because they were treated by only fixed dose of GCs, although we assumed that different levels of anti-metabolite might influence the association of GCs with the final BMD.…”
Section: Discussionmentioning
confidence: 99%
“…35 For examples, genetic variations with genome-wide significance showed poor consistency across GWAS of major depression 36 and allergic rhinitis. 37 Hence, we looked for evidence of replication of SNPs from our first GWAS. Secondly, the ALL population was not ideal to reveal interactive effects of SNP and the cumulative dose of GCs, because they were treated by only fixed dose of GCs, although we assumed that different levels of anti-metabolite might influence the association of GCs with the final BMD.…”
Section: Discussionmentioning
confidence: 99%
“…2.0 software (Sequenom Inc., San Diego, CA, USA), and primers were obtained from Metabion GmbH (Martinsried, Germany). Genotypes were determined using the Sequenom MassARRAY MALDI‐TOF system . A total of 39 SNPs were successfully analyzed with a total genotyping rate of 98%, 1 SNP (rs6586513) did not genotype well and had >10% missing values, and 7 SNPs (rs7617456, rs9860547, rs6932730, rs4724100, rs4410871, rs10893845, and rs9303280) failed in assay design.…”
Section: Methodsmentioning
confidence: 99%
“…Allergic rhinitis (AR) is characterized by symptoms such as watery eyes, sneezing, and rhinorrhea, coupled with a strong association with allergic sensitization (AS), that is, the presence of allergen‐specific immunoglobulin E. The heritability of AR is high and has been estimated to 0.66–0.78 . Although a large number of candidate gene studies mostly analyzing smaller populations have reported associations with AR, few of these have been convincingly replicated . Recently, three genomewide association metastudies (meta‐GWASs) have been reported in different European and North American study populations.…”
mentioning
confidence: 99%
“…Genomic DNA was extracted from blood collected in EDTA using QIAamp DNA Blood Maxi or Mini kits (Qiagen, Hilden, Germany) and DNA concentrations determined by fluorometry using PicoGreen (Molecular Probes, Invitrogen, Eugene, OR, USA). The Swedish study population has previously been analyzed in several AR studies [4,15-17]. The Singapore Chinese population consists of 448 AR patients (250 female, 198 male) and 462 control individuals (337 female and 125 male) and was collected in Singapore between 2008 and 2010.…”
Section: Methodsmentioning
confidence: 99%
“…A large number of studies have identified more than 100 single nucleotide polymorphisms (SNPs) associated with AR, but few of them have been successfully replicated. The general reproducibility of a majority of these AR associations was found to be low in a previous study [4]. Only one genome-wide association study (GWAS) has been performed to identify genetic variants specifically for AR [5].…”
Section: Introductionmentioning
confidence: 99%